2003
DOI: 10.1007/s00122-002-1133-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fusarium head blight resistance QTL in a wheat population using bulked segregant analysis

Abstract: A population of 218 recombinant inbred lines (RILs) was developed from the cross of two wheat (Triticum aestivum L.) cultivars, 'Ning 894037' and 'Alondra'. Ning 894037 has resistance to Fusarium head blight (FHB) and Alondra is moderately susceptible. Response of the RILs and their parental lines to FHB infection was evaluated with point inoculation in four experiments both in greenhouse and in field conditions. Distribution of disease severity in the population is continuous, indicating quantitative inherita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 16 publications
8
82
0
1
Order By: Relevance
“…Second, the parental genotype of RILs in the QTLs on chromosomes 3BS and 5AS affected the FHB spread, percentage of FDKs, and concentration of DON. The positive effect of these QTLs on FHB resistance is consistent with the results of many studies conducted against various genetic backgrounds and environments (Anderson et al 2001, Buerstmayr et al 2003, McCartney et al 2007, Miedaner et al 2006, Nishio et al 2008, Shen et al 2003, Waldron et al 1999, Wilde et al 2007. Our findings confirmed that these QTLs are indispensable to increase FHB resistance in wheat.…”
Section: Discussionsupporting
confidence: 91%
“…Second, the parental genotype of RILs in the QTLs on chromosomes 3BS and 5AS affected the FHB spread, percentage of FDKs, and concentration of DON. The positive effect of these QTLs on FHB resistance is consistent with the results of many studies conducted against various genetic backgrounds and environments (Anderson et al 2001, Buerstmayr et al 2003, McCartney et al 2007, Miedaner et al 2006, Nishio et al 2008, Shen et al 2003, Waldron et al 1999, Wilde et al 2007. Our findings confirmed that these QTLs are indispensable to increase FHB resistance in wheat.…”
Section: Discussionsupporting
confidence: 91%
“…6). The positive effect of these QTLs on FHB resistance is consistent with the results of many previous studies conducted under various genetic backgrounds and environments 1,8,27,31,35,42,50,52,62 . Our findings confirmed that the genotype of QTL, which is located on 3BS of 'Saikai 165' and 'Sumai 3,' is vital for increasing FHB resistance in wheat.…”
Section: Type II Resistancesupporting
confidence: 90%
“…BSA has been successfully used in the mapping of single major genes (Barua et al 1993;Villar et al 1996;Quarrie et al 1999;Shen et al 2003), but a combination of BSA and the candidate genes approach could be very effective in discovering genes with a significant effect on QTLs (Angaji, 2009). …”
Section: With Various Concentrations Of No3mentioning
confidence: 99%